(untitled) (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2021)
Research typically employs essentialist and static representations of masculinity to deal with of male violence against women. Masculinity is thereby linked to pre-social phenomena, naturalized categories, and to identity configurations that are defined as dangerous, due to biological, ethno-racial or class characteristics/configurations. Conversely, a sociologically oriented critical criminology concerned in the relationship between masculinity and crime should interrogate the ways in which, at the social level, committing a deviant or criminal conduct is intertwined with achieving male status and power. We will thus re-read the issue of violence against women as a male problem, that is, as something emerging during the production of masculinity, neither an inherent quality of specific males nor the effects of ethnic belonging or belonging to a lower class, made up of naturally aggressive, violent, and criminal subjects. Rather, we will try to understand the ways in which aggression, violence, and criminal conduct should be read through the lens of the processes through which masculinity is socially constructed. This implies considering the different masculinities involved, and in turn, the role of processes of racialisation and evaluations by groups that alongside their different (middle-) class positionings.